ENGARUH PEMBERIAN EKSTRAK UBI JALAR (Ipomoea batatas L.) VARIETAS UNGU KULTIVAR GUNUNG KAWI TERHADAP KADAR GAMMA – GT PADA TIKUS WISTAR PUTIH JANTAN (Rattus norvegicus strain wistar) YANG DIBERI DIET ATEROGENIK - dr. A A Ngurah Wisnu Adiputra C. (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Hyperlipidemia is a condition in which increased levels of serum cholesterol or triglycerides above the normal limits due to excessive consumption of fat, causing fat intake and an overhaul becomes unbalanced. Purple sweet potato contains anthocyanins, flavonoids, and fiber Anthocyanins and flavonoids can lower triglyceride levels. This study aims to determine the effect of extract of sweet potato (Ipomoea batatas L.) cultivars Purple varieties Gunung Kawi Gamma GT levels Against White Male Wistar rats were given the atherogenic diet. This study was designed using pure experimental analytic methods Randomized Post Test Only Control Group Design. Population of this research is a white male Wistar rats (Rattus norvegicus Wistar) in healthy condition are 2-3 months old weighing approximately 150-250 grams. Number of samples of 5 mice in each treatment group so that the total number of samples required are as many as 25 rats.The results showed that the extract of purple sweet potato (Ipomoea batatas L.) cultivars Gunung Kawi proved to have an influence on a reducing Gamma-glutamyl transferase levels in male rats (Rattus norvegicus) strain wistar were given atherogenic diet with doses of about 20 mg/kg.